EVALUATION OF PUBLIC HEALTH MESSAGES TO PROMOTE EARLY DETECTION OF DEMENTIA AMONG ADULT LATINO CHILDREN. (16th November 2018) - Moraes Balbim, G; Aguirre, K; Zavala, M; Davila, K; Marquez, D
Abstract: The stigmatization of dementia, combined with cultural norms, can be barriers to early detection and treatment for older adults from minority groups. Public health messaging is an approach for increasing awareness to seek early detection. This study evaluated how such messages were received by adult Latino children with a living older parent. Messages encouraging adult children to accompany their parent for a cognitive assessment were assessed in four focus groups. Each message had a tagline, a call to action, and a photo. Participants were 24 adult Latino children (13 male, 11 female) aged 26–61 years old. Data were transcribed and coded, and thematic analysis was conducted. Before taking action, adult children wanted more information on the reasons to seek cognitive evaluation. The conversation to encourage their parents to get a cognitive evaluation was judged as difficult because discussing cognitive and mental health is taboo in Latino culture. The taglines (e.g., "Be there for them now, like they were there for you then") had mixed perceptions; some were judged as vague, produced guilt, and were mismatched with the photo or call to action. Participants indicated the necessity to translate all messages to Spanish. Feedback on the photos related to the need to be more natural, a balance between positive and serious facial expressions, show more diversity and more family members, and depict sentimental memories that are culture‐specific around food or sport. This study provides important information to adapt public health messages to be more effective encouraging early dementia detection in Latinos.